2015
DOI: 10.4278/ajhp.140123-qual-43
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Using Treadmill Workstations under Real Working Conditions: A Qualitative Study in Female Office Workers

Abstract: In this female group, treadmill workstations had serious design problems for workers with not enough control of their jobs. The early identification and removal of barriers likely needs to be considered when offering these workstations to workers with low job autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 61 publications
3
28
1
Order By: Relevance
“…The emerging qualitative evidence base for the impact of workplace sitting interventions is varied and includes evaluations of activity-permissive workstations (Grunseit et al, 2013;Chau et al, 2014;Cifuentes et al, 2015), computer- (Cooley et al, 2014;Mackenzie et al, 2015) or web-based programmes (Bort-Roig et al, 2014), and activity booster breaks (Taylor et al, 2013). Despite these different intervention approaches, common key themes on facilitators of workplace sitting reduction include the importance of a supportive social environment, management support, raised awareness of both sitting habits and the health impacts of sitting, and feedback on behaviour (Taylor et al, 2013;Bort-Roig et al, 2014;Chau et al, 2014;Cooley et al, 2014;Cifuentes et al, 2015;Mackenzie et al, 2015). Barriers have included the perceived negative views of peers and managers, time pressures and workload, and the suitability of strategies for work tasks (Grunseit et al, 2013;Bort-Roig et al, 2014;Chau et al, 2014;Cifuentes et al, 2015;Mackenzie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The emerging qualitative evidence base for the impact of workplace sitting interventions is varied and includes evaluations of activity-permissive workstations (Grunseit et al, 2013;Chau et al, 2014;Cifuentes et al, 2015), computer- (Cooley et al, 2014;Mackenzie et al, 2015) or web-based programmes (Bort-Roig et al, 2014), and activity booster breaks (Taylor et al, 2013). Despite these different intervention approaches, common key themes on facilitators of workplace sitting reduction include the importance of a supportive social environment, management support, raised awareness of both sitting habits and the health impacts of sitting, and feedback on behaviour (Taylor et al, 2013;Bort-Roig et al, 2014;Chau et al, 2014;Cooley et al, 2014;Cifuentes et al, 2015;Mackenzie et al, 2015). Barriers have included the perceived negative views of peers and managers, time pressures and workload, and the suitability of strategies for work tasks (Grunseit et al, 2013;Bort-Roig et al, 2014;Chau et al, 2014;Cifuentes et al, 2015;Mackenzie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One study noted that workers most affected by diseases associated with sedentary jobs also had the lowest levels of autonomy at work. This study also noted job autonomy as the greatest facilitator of acceptance of active workstations [Cifuentes et al 2015].…”
Section: Potential Barriers To Reducing Sedentary Time At Workmentioning
confidence: 99%
“…Employers should consider the following TWH concepts to reduce workers' sedentary time while at work [CDC 2014;Cifuentes et al 2015;OHSU 2014;NIOSH 2015d;Goetzel and Ozminkowski 2008;Morse et al 2012;Goetzel et al 2014;HHS 2008HHS , 2016Waters and Dick 2014;Robertson et al 2002;Grandjean 1988]:…”
Section: Concepts Into Workplace Safety and Health Programsmentioning
confidence: 99%
“…A total of five participants declined to participate in the interviews; one from the first group and four from the second group. For these interviews, we used a semi-structured interview guide (S1 Table) drawn from earlier research [9] with the aim of gaining deeper insight into the respondents' experiences of the treadmill workstation. Four female interviewers, all from the field of physiotherapy, conducted these interviews: one researcher with great experience in conducting interviews, while the other three were students (one was a PhD-student) with limited experience of conducting interviews.…”
Section: Interview Data Collectionmentioning
confidence: 99%
“…The results suggested that common barriers were related to office desk setup and the effect of the walking noise on communication. Facilitators included the feeling of enjoyment and more energy after using the treadmill for a period of time [9]. In another study in a health insurance company, researchers investigated adherence issues during implementation of shared treadmill workstations for 6 months among office workers with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%